Political Paths of the Croatian Participants at the Prague Congress of the Slavs in 1848 - Ostajmer, Branko; Švoger, Vlasta (Historical Studies on Central Europe, 2025)
The starting point of this study is the reception of Austroslavism in mid-nineteenth-century Croatian politics, especially during the 1848–1849 revolutionary years. Austroslavism as a political concept aspiring to preserve the Habsburg Monarchy and remodel it into a federation based on the ethnic-linguistic principle, became a major component of the 1848–1849 Croatian political movement. In the second part of the study, the participation of Croatian representatives at the 1848 Congress of the Slavs in Prague is discussed. The ten Croatian delegates in Prague were politicians, intellectuals, and artists. Three of them were elected by the Zagreb People’s Assembly to be the Croatian representatives at the Congress in Prague, and the others were students in Vienna or in Prague at the time. They were trying to uphold the Austro-Slavic spirit of the Congress and enforce the Congress’s main constitutional goals in their political, publicist or artistic work in the following years. However, although some of them played a significant role in Croatian political life in the 1848–1849 as publicists and even as members of the Ban’s Council, the first Croatian Government operating from May 1848 to June 1850, they were unable to achieve the Congress’s political and constitutional goals. Even the idea of resuming the Congress of the Slavs in Zagreb, as well as the 1851-year proposition of the Croatian cultural organisation Matica ilirska to organize the conference of Slavic philologists in a Slavic capital, were dropped due to the political circumstances. The study then traces the development of the ideological and political life paths of individuals: Dragojlo Kušlan, Josip Praus, Mato Topalović, Andrija Torkvat Brlić, Maksimilijan Prica, Stanko Vraz, Vatroslav Lisinski, Dr. Miroslav Dražić, Jakob Franjo Tkalec, and Petar Frančeskini. Except for the latter two, they were well-known and active in the political and (or) cultural life of nineteenth-century Croatia. Their political thoughts in the 1848–1849 revolutionary years and in subsequent decades are analysed. Overall, a panorama of the political ideas, together with the careers of these people, is presented. Although disappointed with neo-absolutism, some played a significant role in Croatia’s political life in the years following the reestablishment of the constitutional system in the Habsburg Monarchy.